PENGARUH SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK CAMILLE PADA GENERASI Z DI SURABAYA - Alifa Nurlaily; Ayun Maduwinarti; Awin Maduwinarti (Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2024)
Internet quality improvement in Indonesia made Indonesian people used social media more frequently. One of the most used social media is Instagram. This is a chance for Indonesian business owner to do online marketing using Social Media Marketing. One brand that use social media marketing actively is Camille. Social media marketing are expected to improve communication between brand and consumer. Good brand communication will increase the brand purchase decision. Social media marketing process includes 3 main indicator that is Content Creation , Content Sharing, dan Connecting. The effectiveness of those 3 indicators will have significant impact on brand purchase decision. This study wants to test about the effect of social media marketing on purchase decision of Camille in Z generation in Surabaya. The data in this study are collected using google form with 100 total sample. Analysis Technique that used in this study are double linear regression, classic assumption test, F test, t test, and hypothesis test. Result shows that social media marketing has significant impact on purchase decision Camille product